Delayed-onset bleb-associated endophthalmitis: presentation and outcome by culture result - Jacobs DJ (Dove Medical Press, 2011)
David J Jacobs, Theodore Leng, Harry W Flynn Jr, Wei Shi, Darlene Miller, Steven J GeddeDepartment of Ophthalmology, Bascom Palmer Eye Institute, Miller School of Medicine, University of Miami, FL, USAPurpose: To determine how culture results are associated with clinical presentations and outcomes in delayed-onset bleb-associated endophthalmitis (BAE).Methods: Retrospective consecutive case series of BAE at Bascom Palmer Eye Institute between January 1, 1996 and December 31, 2009. All patients had prior glaucoma filtering surgery. BAE was defined as intraocular infection with vitreous involvement receiving treatment with intravitreal antibiotics. Visual acuity (VA) outcomes and other clinical data were grouped by culture result and compared using the 2-sided Student's t-test.Main outcome measure: Mean logMAR change at 3 months after treatment (3-month logMARΔ).Results: Eighty-six eyes of 85 patients were identified. Two eyes were primarily eviscerated. Fifty-three (63%) eyes were culture-positive with the following organisms: Streptococcus, 21 (25%); coagulase-negative Staphylococcus, 9 (11%); Enterococcus, 6 (7%); Gram-negative, 15 (18%); Moraxella, 8 (10%); Pseudomonas, 3 (4%); and Serratia, 3 (4%). Presenting logMAR VA: culture-positive worse than culture-negative cases (2.45 vs 2.19, P = 0.05). Presenting intraocular pressure (IOP): culture-positive higher than culture-negative cases (24 mmHg vs 14 mmHg, P = 0.002). Poor presenting view of the fundus: Streptococcus worse than coagulase-negative Staphylococcus cases (90% vs 44%, P = 0.006), Pseudomonas and Serratia worse than Moraxella cases (100% vs 50%, P = 0.04). Three month logMARΔ: culture-positive worse than culture-negative cases (1.03 vs 0.43, P = 0.02), Streptococcus worse than coagulase-negative Staphylococcus cases (1.44 vs 0.31, P = 0.004), Pseudomonas and Serratia worse than coagulase-negative Staphylococcus cases (2.41 vs 0.31, P = 0.001), Pseudomonas and Serratia worse than Moraxella cases (2.41 vs 0.04, P = 0.001). A culture result of Streptococcus or Serratia was present in 6 of 7 eyes that received an additional treatment of enucleation or evisceration (P = 0.01).Conclusion: Culture-positive cases were associated with worse presenting VA, higher presenting IOP, and worse VA outcomes than culture-negative cases. Streptococcus, Pseudomonas, and Serratia cases were associated with poor presenting view of the fundus and worse VA outcomes than coagulase-negative Staphylococcus and Moraxella cases.Keywords: endophthalmitis, bleb-associated endophthalmitis, trabeculectomy, culture results